Correct scientific name of the man man tim plant is Cleome rutidosperma D. C. (Capparaceae Juss.) - Thuong, Sy Danh; Bach, Tran The (Academia Journal of Biology, 2014)
According to Jacobs, the genus Cleome L. had about 150 species in the world. There were 4 cleome species in Vietnam: C. viscosa L., C. rutidosperma DC., C. gynandra L. and C. spinosa Jacq.. Some species were used as medicinal plants and vegetables (C. gynandra, C. viscosa); some species had beautiful flowers (C. spinosa). In Vietnam, many botanists had determined the “man man tim” plant as C. chelidonii L. f.. It was not correct and was C. rutidosperma DC.. We have established a table to compare some characters of and C. chelidonii and C. rutidosperma with specimens collected in Vietnam. We have discribed C. rutidosperma DC. and built a key to classify 4 species of the genus Cleome L. known in Vietnam.